2005
DOI: 10.1038/sj.bjc.6602611
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and mortality in patients with insulin-treated diabetes: a UK cohort study

Abstract: Raised risks of several cancers have been found in patients with type II diabetes, but there are few data on cancer risk in type I diabetes. We conducted a cohort study of 28 900 UK patients with insulin-treated diabetes followed for 520 517 person-years, and compared their cancer incidence and mortality with national expectations. To analyse by diabetes type, we examined risks separately in 23 834 patients diagnosed with diabetes under the age of 30 years, who will almost all have had type I diabetes, and 506… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
170
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 44 publications
4
170
0
3
Order By: Relevance
“…Of these 25 studies, five were cohort studies that used incidence and/or mortality rate ratios as the measure of RR [9,21,[24][25][26] (Table 1), 13 were case-control studies [10-20, 22, 23] (Table 2) and seven were cohort studies that used standardised incidence and/or mortality ratio as the measure of risk [34][35][36][37][38][39][40] (Table 3). Twelve studies were conducted in the USA, ten in Europe, one in South America and one in Asia.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these 25 studies, five were cohort studies that used incidence and/or mortality rate ratios as the measure of RR [9,21,[24][25][26] (Table 1), 13 were case-control studies [10-20, 22, 23] (Table 2) and seven were cohort studies that used standardised incidence and/or mortality ratio as the measure of risk [34][35][36][37][38][39][40] (Table 3). Twelve studies were conducted in the USA, ten in Europe, one in South America and one in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…These 16 studies had 96,003 participants. The four cohort studies [34,[36][37][38] that reported standardised incidence ratios were analysed separately. For the meta-analysis of diabetes and endometrial cancer mortality, we included the two cohort studies that reported mortality rate ratio [21,26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations